Legal Protection and Empowerment of Vulnerable Adults - Kovaček Stanić, Gordana; Samardzic, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Having in mind demographic trends and especially growing number of the population in the old age, it is very important that family law deals with the needs of the vulnerable adults. In 2021 in Serbia the percentage of the population aged 65 and older is 21.3%. The number of users in Centres for social work that are deprived of ‘transactional’ (‘contractual’) capacity is growing (in 2017 13.075 persons are deprived of the ‘transactional’ (‘contractual’) capacity). In this paper authors analyse legal changes in the procedural law which aim is protection and empowerment of vulnerable adults. One solution is limitation of the deprivation of ‘transactional’ (‘contractual’) capacity in a way that the decision is to be to re-examine in the period of maximum three years (Law on Non-Contentious Proceedings amendments 2014). Other solution is the obligation of the court to define legal operations which the person deprived of the capacity can undertake by himself/herself and especially if this person can exercise his/her elective right (Law on Non-Contentious Proceedings amendments 2022). The authors analyse proposed legal changes in the family law which aim is . The recent Draft Law on Amendments to Family Act empowers vulnerable adults in the several ways. It is proposed to abandon the existing institution of “deprivation of legal capacity“ and to keep only the institution of the “limitation of legal capacity“. It is proposed that court in the decision on limitation of ‘transactional’ (‘contractual’) capacity should determine the legal operations that a person partially deprived of capacity may not undertake independently. The Draft Law on Amendments to Family Act adds the legal acts to legal operations which the person deprived of capacity may undertake. This solution empowers vulnerable adults giving them wider circle of independent rights. It is proposed that the guardianship authority is obliged to protect the dignity and well-being of the ward; try to limit the rights of the ward as little as possible; encourage the ward’s independent decision-making; provide him/her support in decision-making, as well as the participation in community life; take into account all the specifics of the ward’s personality and accept his decisions, opinions, wishes, and attitudes, unless it is in conflict with the welfare of the ward. In addition, it is proposed to stipulate the guardian’s obligation to make sure that the adult ward receives all the information on issues that concern him/her in a timely manner and to take into account in the utmost extent possible the ward’s decisions, opinion, wishes and attitudes when performing the guardian’s duties.